login
A107256
a(n) = n^6 - 63*n + 63, with n*a(n) + n*(n-1)*63 = n^7.
0
1, 1, 603, 3907, 15373, 46341, 117271, 261703, 530937, 999433, 1770931, 2985291, 4826053, 7528717, 11389743, 16776271, 24136561, 34011153, 47044747, 63998803, 85764861, 113378581, 148034503, 191101527, 244139113, 308914201, 387418851
OFFSET
1,3
EXAMPLE
a(2) = 1, 1 + 127 = 2^7; a(3) = 603, 603 + 729 + 855 = 3^7; a(4) = 3907, 3907 + 4033 + 4159 + 4285 = 4^7.
CROSSREFS
Sequence in context: A348077 A066785 A178032 * A177685 A250907 A209550
KEYWORD
nonn
AUTHOR
Andras Erszegi (erszegi.andras(AT)chello.hu), May 14 2005
STATUS
approved